Women's access to land and housing post-1994 in the informal settlements at Ficksburg in the Free State South Africa - Kane, Mookho (Department of Social Development, 2014)
This dissertation investigated the constraints that inhibit women from getting access to formal housing and land in Ficksburg in the Free State province of South Africa. The study sought to substantiate the hypothesis that inequalities within South African societies have been aggravated by gender dynamics and conservative macro-economic development agendas in post-apartheid South Africa in the form of development programmes like the Redistribution and Development Programme (RDP), Growth Employment and Redistribution (GEAR), as well as Building New Ground (BNG). Throughout the study, women were viewed from a marginalisation perspective. This study relies heavily on qualitative research methods. The instruments used for data collection were semi-structured interviews and participant observation. The interviews were conducted with fifteen women dwelling in shacks that are legally located in those settlements, ten women dwelling in Masak'hane/RDP houses, five women living in shacks in the informal settlements, but illegally located, and six women living in the informal settlements in self-built houses, as well as the Senior Manager at Setsoto Municipality Department of Housing. The practical and strategic gender needs of women were also used to analyse the situation of women in the informal settlements. The main findings of this study revealed that large numbers of participants do not have financial backup, and that made them ineligible to meet the requirements of the financial institutions for housing funds. Low wages limited women from getting access to land and housing from the market like their male counterparts. Along with this, constitutional laws, customary laws and registration of title deeds seemed to have complicated women's access to land and houses. Low standards of education, lack of knowledge, age and absence of identity documents were found to be other constraints. Although women in all categories struggled to get access to land and formal housing in Ficksburg informal settlements. The findings revealed that single, separated women and women under 21years struggled more than old, divorced and married women.